2019
DOI: 10.2754/avb201988030271
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hCG, GnRH and PGF2α analogue cloprostenol on the oestrus cycle in jennies

Abstract: The objectives of this study were twofold. Firstly, the present study was designed to examine susceptibility of the corpus luteum (CL) in early diestrus in jennies; and secondly, to investigate the effect of two commonly used hormonal agents in horses on the induction of ovulation in jennies. The oestrus cycles of eleven jennies were monitored by ultrasound every day. When the dominant follicle reached a diameter of 30 mm, the jennies were treated by intramuscular administration of gonadotropin-releasing hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…There are several hormones that can be used to induce ovulation in equine species [ 30 , 31 ], such as human Chorionic Gonadotropin (hCG), Equine Pituitary Extract (EPE) and Gonadotropin-Releasing Hormone (GnRH). Although the efficacy of both EPE and GnRH in hastening ovulation has been widely proven in mares [ 26 , 28 , 30 , 32 , 33 , 34 ], hCG is still the most popular inductor, not only in mares [ 27 , 30 , 31 ], but also in jennies [ 35 , 36 ], due to its high efficacy, easier commercial availability and lower cost. However, various studies have shown that repeated administration of this hormone can stimulate the synthesis of anti-hCG antibodies, leading to a loss of its effectiveness [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several hormones that can be used to induce ovulation in equine species [ 30 , 31 ], such as human Chorionic Gonadotropin (hCG), Equine Pituitary Extract (EPE) and Gonadotropin-Releasing Hormone (GnRH). Although the efficacy of both EPE and GnRH in hastening ovulation has been widely proven in mares [ 26 , 28 , 30 , 32 , 33 , 34 ], hCG is still the most popular inductor, not only in mares [ 27 , 30 , 31 ], but also in jennies [ 35 , 36 ], due to its high efficacy, easier commercial availability and lower cost. However, various studies have shown that repeated administration of this hormone can stimulate the synthesis of anti-hCG antibodies, leading to a loss of its effectiveness [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%